Microstructure evolution during warm deformation of low carbon steel with dispersed cementite - Gallego, J. [UNESP]; Jorge, A. M.; Balancin, O. (Trans Tech Publications, 2007)
The microstructure evolution and mechanical behavior during large strain of a 0.16%C-Mn steel has been investigated by warm torsion tests. These experiments were carried out at 685°C at equivalent strain rate of 0.1 s . The initial microstructure composed of a martensite matrix with uniformly dispersed fine cementite particles was attained by quenching and tempering. The microstructure evolution during tempering and straining was performed through interrupted tests. As the material was reheated to testing temperature, well-defined cell structure was created and subgrains within lath martensite were observed by TEM; strong recovery took place, decreasing the dislocation density. After 1 hour at the test temperature and without straining, EBSD technique showed the formation of new grains. The flow stress curves measured had a peculiar shape: rapid work hardening to a hump, followed by an extensive flow-softening region. 65% of the boundaries observed in the sample strained to ε = 1.0 were high angle grain boundaries. After straining to ε = 5.0, average ferrite grain size close to 1.5 μm was found, suggesting that dynamic recrystallization took place. Also, two sets of cementite particles were observed: large particles aligned with straining direction and smaller particles more uniformly dispersed. The fragmentation or grain subdivision that occurred during reheating and tempering time was essential for the formation of ultrafine grained microstructure.
Keywords: Martensite; Ultrafine grain; Warm deformation; Carbon steel; Microstructure; Torsion testing; Deformation